Remotely supervised online cognitive training to reduce cognitive difficulties following chemotherapy in patients treated for localized breast cancer: Protocol of the Cog-Stim2 multicenter randomized controlled trial - Marie Bousquet; Marie Lange; Justine Lequesne; Isabelle Durand-Zaleski; Olivia Diaz; Antonio Di Meglio; Thomas Bachelot; Jean-Michel Grellard; Bénédicte Clarisse; Florence Joly (PLoS ONE, 2025)
Introduction Chemotherapy-related cognitive impairment (CRCI) is frequently reported by breast cancer patients. Cognitive training is considered as one of the most effective approaches for improving cognitive function in patients with CRCI. As implementing cognitive training programs in healthcare centers remains challenging, online cognitive training appears to be an effective way to manage CRCI. Furthermore, supervision by a cognitive health specialist may increase motivation, adherence and effectiveness. However, the added benefit of combining supervision by health specialist with online cognitive training has not been studied in cancer patients. Method Cog-Stim2 is a nationwide prospective multicenter randomized trial that aims to evaluate, in patients with localized breast cancer treated with chemotherapy who have cognitive complaints (n = 300), the benefits of a 12-week online cognitive training program (HappyNeuron®) supervised remotely by a neuropsychologist (experimental group) on cognitive complaints compared to open acess to the same cognitive training program for 12 weeks without supervision (active control group). Cognitive, associated factors, and biological assessments will be performed at baseline, at the end of the intervention, and 3 and 9 months later. The primary endpoint is the change in patients’ cognitive complaints (FACT‐Cog). The main secondary endpoints are objective cognitive functionning (CNS-VitalSign®), anxiety/depression (HADS), fatigue (FACIT-F) and sleep (ISI). The supervised sessions will be structured around patient’s difficulties and goals, and will include educational content (psychoeducation) on CRCI, the brain, cognition, and cognitive strategies to use in daily life. The medico-economic impact of the intervention will be also assessed. Discussion The results will provide information on the additional benefits of combining remote supervision by experts with online cognitive training in a 12-week cognitive training program for breast cancer patients with CRCI. Our long-term goal is to generalize this type of intervention into clinical practice for patients with CRCI. Clinical trial registration ClinicalTrials.gov identifier: NCT06027632, registered on 08/31/2023